Internet connectivity disruption in Azerbaijan (Azerbaijan) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity mixed detected in Azerbaijan. Data sourced from IODA, CensoredPlanet.
Censorship Incident ID: AZ-2026-0122. Severity: critical. Confidence: 67%